El presupuesto participativo del Gobierno Autónomo Descentralizado de Saraguro, período 2014-2019 y su incidencia en el cumplimiento de las necesidades básicas insatisfechas en la parroquia Manú en el indicador de acceso a servicios básicos - Armijos Sisalima, Ángel Arnoldo (2022)
The present research work entitled "The participatory budgeting of the Municipal Autonomous Decentralized Government of Saraguro and its impact on the implementation of unsatisfied basic needs (UBN) in the parish of Manú and on the access to basic services indicator" aims to contribute to the reduction of UBN, namely, drinking water and wastewater services in the aforementioned parish based on adequate management of the economic resources coming from the central government. A mixed methodology was used in this research, where quantitative and qualitative information concerning the distribution of the resources of the Municipal Government through the macro project approach was obtained. The information was collected from the previously mentioned governmental entity. Finally, an interview was conducted with the members of the Municipal Council to assess the feasibility of the implementation of a public policy in the institution. The MADG of Saraguro did not carry out any participatory budgeting from 2014 to 2019. The works in the Manú parish, according to the access to basic services indicator, were executed via macro projects and were based on unsatisfied basic needs (UBN). The resources invested in by the MADG of Saraguro contributed to the reduction of the UBN in the beneficiary communities. Finally, it is recommended that the MADG implement a public policy of citizen participation aimed at promoting the fair, equitable and inclusive distribution of economic resources from the central government.